Medical and Psychological Morbidity of Patients with Urogenital Fistula - Srichand, Pushpa; Hassan, Nabila; Syed, Sher Shah; Farheen, Gul (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aim: This study aimed to determine the frequency of medical and psychological morbidity of patients with urogenital fi stulae. Methods: It was a descriptive study carried out at Liaquat University Hospital and Isra University Hospital, Hyderabad, Pakistan from 01/06/2007 to 30/06/2018, where 520 patients with urogenital fi stulae were managed. A pre-designed proforma was used to record the details about medical and psycho-social consequences. Data was analyzed, and results were described as frequency and percentages. Results: Among 16759 gynecological admissions, 520 (3.1%) were confi rmed cases of urinary fi stulae. Average age of patients was 31±2.8 years and average parity was 3±2.4. Regarding health consequences, all patients had major degree depression. Majority (88%) of the patients were malnourished. Severe excoriation of vulva and inner thighs was seen in 338 (65%) patients. Vaginal stenosis, vaginal and vesical calculi were other medical problems. Almost all (n= 511, 98%) patients were found to be socially isolated. 62% patients kept themselves restricted to home, with avoidance of family gatherings and travelling. Marital breakdown seen in 81% (n=241). 90% of patients quit their job. Majority of them suff ered social, verbal or physical abuse. Conclusions: Patients with urogenital fi stulae not only havesurgical morbidity, they also do suff er from signifi cant medical and psychosocial morbidity. There is a defi nite need to address these under-looked miseriesby a devoted fi stulae team working in collaboration with social workers, religious leaders and healthcare providers.